Birth Weight, Insulin Resistance, and Blood Pressure in Late Preterm Infants - Aly, Hany; Soliman, Reem M.; El-Dib, Mohamed; Fawzy, Enas M.; Badawi, Nora E.; Rabie, Walaa A.; Elbadawi, Ayman A. (American Journal of Perinatology, 2015)
Objectives This study aims to compare insulin sensitivity, lipid profile, and blood pressure in late preterm infants born at appropriate for gestational age (AGA) and small for gestational age (SGA).Study Design We conducted a prospective, observational study on AGA and SGA late preterm infants. Blood pressure, fasting blood glucose, insulin, insulin-like growth factor 1 (IGF-1), insulin resistance, and lipid profile were measured on the 1st day and in the 2nd week of life.Results Overall 81 infants (41 AGA and 40 SGA) were included in the study. At the time of enrollment, there was no difference in blood pressure, insulin resistance, and lipid profile. At follow-up SGA patients had significantly decreased diastolic blood pressure (48 ± 11 mm Hg vs. 42 ± 11 mm Hg, p = 0.04), and decreased IGF-1 (139 ng/mL [119–153] vs. 124 ng/mL [115–138], p = 0.05). No linear association was found between the insulin resistance and either birth weight percentile, day of life, or average 1st week daily caloric intake.Conclusion As compared with AGA, SGA late preterm infants had lower diastolic blood pressure and lower IGF-1 during the 2nd week of life, but similar insulin resistance and lipid profile. We speculate that although metabolic derangements in SGA infants could have occurred at a much earlier age in fetal life, their manifestations may not be present in the immediate postnatal life.
Keywords: glucose; SGA; metabolic syndrome; premature; nutrition